CDR3β sequence motifs regulate autoreactivity of human invariant NKT cell receptors. (April 2016) - Chamoto, Kenji; Guo, Tingxi; Imataki, Osamu; Tanaka, Makito; Nakatsugawa, Munehide; Ochi, Toshiki; Yamashita, Yuki; Saito, Akiko M.; Saito, Toshiki I.; Butler, Marcus O.; Hirano, Naoto
Abstract: Invariant natural killer T (iNKT) cells are a subset of T lymphocytes that recognize lipid ligands presented by monomorphic CD1d. Human iNKT T cell receptor (TCR) is largely composed of invariant Vα24 (Vα24i) TCRα chain and semi-variant Vβ11 TCRβ chain, where complementarity-determining region (CDR)3β is the sole variable region. One of the characteristic features of iNKT cells is that they retain autoreactivity even after the thymic selection. However, the molecular features of human iNKT TCR CDR3β sequences that regulate autoreactivity remain unknown. Since the numbers of iNKT cells with detectable autoreactivity in peripheral blood is limited, we introduced the Vα24i gene into peripheral T cells and generated a de novo human iNKT TCR repertoire. By stimulating the transfected T cells with artificial antigen presenting cells (aAPCs) presenting self-ligands, we enriched strongly autoreactive iNKT TCRs and isolated a large panel of human iNKT TCRs with a broad range autoreactivity. From this panel of unique iNKT TCRs, we deciphered three CDR3β sequence motifs frequently encoded by strongly-autoreactive iNKT TCRs: a VD region with 2 or more acidic amino acids, usage of the Jβ2-5 allele, and a CDR3β region of 13 amino acids in length. iNKT TCRs encoding 2 or 3 sequence motifs also exhibit higher autoreactivity than those encoding 0 or 1 motifs. These data facilitate our understanding of the molecular basis for human iNKT cell autoreactivity involved in immune responses associated with human disease. Highlights: Introducing Vα24i gene to peripheral T cells generates a novel iNKT TCR repertoire. Stimulation by unloaded aAPCs enriches strongly autoreactive iNKT TCR transfectants. A large panel of human iNKT TCRs with a broad range autoreactivity are isolated. Three CDR3β sequence motifs associated with high autoreactivity are identified. Human iNKT TCRs encoding 2 or 3 sequence motifs exhibit higher autoreactivity.